Improvement and optimization of tire nut removal with 114 PCD - Azizul Rahman, Abd Aziz (2008)
Vehicle is an important machine in human daily life. Nowadays, each family has at least one car to make the transportation easy and faster. For a car, the tool set-up for each vehicle is a T-nut wrench and car jacker which is hard to use for a women or teen to open their car’s nut. In 2006, a tire nut removal with 114 pitch circle diameter has been developed to replace T-nut wrench that can reduce the force and torque needed to open the nuts and open all four nuts simultaneously. This tool used mild steel as the main material to fabricate a gearing system and the gear ratio is 21.125 gear ratio force reduction. The total weight of the product was 5.5 kg. For this final year project, this tire nut removal has been improved about the weight, cost of production and the gear ratio. The new tire nut removal has 162 gear ratio that convert the force and torque better than the first tire but removal with 2.5 kg total weight. The main material to fabricate the spur gear has been changed to thermoset plastic material that is Nylatron GSM Blue with lighter weight and cheaper compared to the mild steel material. The new gear ratio has convert the torque to 3.45 Nm that can be supported by power window motor that will be used to help the 114 pitch circle diameter car user. The design of this product is demanded to be smaller and compact to make it easy and comfortable for the user. A new tire nut removal with 203 x 203 x 87.5 mm has been designed to make the tire nut removal smaller, lighter and efficient.